ChemInform Abstract: A Mixed Ligand Approach for the Asymmetric Hydrogenation of 2‐Substituted Pyridinium Salts. Issue 52 (6th December 2016) - Renom‐Carrasco, Marc; Gajewski, Piotr; Pignataro, Luca; de Vries, Johannes G.; Piarulli, Umberto; Gennari, Cesare; Lefort, Laurent
Abstract: The title reaction gives 2‐substituted piperidines with full conversion and good enantioselectivity using iridium as catalyst and a mixed ligand of a chiral monodentate phosphoramidite and an achiral phosphine.